Automatic associations of breast cancer and heart disease with fruit and vegetables and physical activity. (August 2019) - Berry, Tanya R; Courneya, Kerry S; Norris, Colleen M; Rodgers, Wendy M; Spence, John C
Objectives: This exploratory research examined if breast cancer or heart disease is automatically associated with physical activity compared to fruit and vegetable stimuli; if reading messages about reducing risk of breast cancer or heart disease through physical activity and fruit and vegetable consumption would affect automatic associations; and if automatic associations were related to intentions to be physically active or consume fruit and vegetables. Methods: Participants were 80 women who completed pretest measures of automatic associations, then read a breast cancer, heart disease, or control message, followed by posttest measures. Results: There was a significant association of breast cancer–related words with fruit and vegetables compared to physical activity. Heart disease was also more strongly associated with fruit and vegetables than physical activity at pretest but not at posttest. There were no other significant findings. Conclusion: This research highlights that fruit and vegetables rather than physical activity are more strongly associated with perceptions of breast cancer and heart disease. Automatic associations are an attitudinal construct, and the strength of association between fruit and vegetables, rather than physical activity, indicates how messages may be processed.